2017
DOI: 10.5935/paet.v10.n01.02
|View full text |Cite
|
Sign up to set email alerts
|

Adubação nitrogenada em arroz cultivado em solos arenosos de várzea tropical

Abstract: O estudo foi conduzido em solo Hidromórfico de várzea irrigada em Formoso do Araguaia-TO, na safra 2011/2012. O delineamento experimental foi em faixas sob esquema fatorial 2x5, com quatro repetições. As doses avaliadas foram 25, 50, 75, 100 e 125 kg ha-1 de N. As características avaliadas foram altura de plantas, número de panículas, produtividade de grãos, massa de cem grãos, teor de nitrogênio e Índice de clorofila total. Os dados foram submetidos à análise de variância e de regressão ao nível de 5% de prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…This trait is highly influenced by environmental conditions. Lopes et al (2017) found that nitrogen doses increased the plant height of two irrigated rice cultivars (Irga 424 and Epagri 116), but without resulting in plant lodging. Sangoi et al (2014) observed that the cultivar Epagri 106 had the smallest height at two evaluation sites (Itajaí and Pouso Redondo, Santa Catarina), which was related to the higher precocity of the cultivar.…”
Section: Resultsmentioning
confidence: 99%
“…This trait is highly influenced by environmental conditions. Lopes et al (2017) found that nitrogen doses increased the plant height of two irrigated rice cultivars (Irga 424 and Epagri 116), but without resulting in plant lodging. Sangoi et al (2014) observed that the cultivar Epagri 106 had the smallest height at two evaluation sites (Itajaí and Pouso Redondo, Santa Catarina), which was related to the higher precocity of the cultivar.…”
Section: Resultsmentioning
confidence: 99%